Influence of the nature and environment of manganese in Mn-BEA zeolites on NO conversion in selective catalytic reduction with ammonia. Issue 21 (17th May 2017) - Baran, R.; Valentin, L.; Krafft, J.-M.; Grzybek, T.; Glatzel, P.; Dzwigaj, S.
Abstract : Manganese-containing BEA zeolites, Mn x SiBEA ( x = 1–4 wt%) and Mn(I.E.) AlBEA, were prepared by a two-step post-synthesis method and a conventional wet ion-exchange, respectively, and applied as catalysts in the selective catalytic reduction of NO with ammonia (NH3 -SCR). Abstract : Manganese-containing BEA zeolites, Mn x SiBEA ( x = 1–4 wt%) and Mn(I.E.) AlBEA, were prepared by a two-step post-synthesis method and a conventional wet ion-exchange, respectively, and applied as catalysts in the selective catalytic reduction of NO with ammonia (NH3 -SCR). The physicochemical analysis of zeolite properties by high-energy-resolution fluorescence-detected XANES (HERFD-XANES) and X-ray emission spectroscopy (XES) uncovered that the coordination, geometry and oxidation state of Mn species are strongly related to the preparation method. Additionally, the study of catalyst acidity by FTIR spectroscopy with CO and pyridine probe molecules provided important insight into the number and type of acidic centres present on the catalyst surface. The catalytic results revealed that NO conversion depended on the state and content of Mn. The zeolites obtained by the two-step post-synthesis method and with a low Mn content were very active in the medium temperature range (NO conversion ∼100%) with simultaneous high selectivity to N2 due to the presence of isolated, framework Mn(iii ) and Mn(ii ) species. The N2 O formation was especially high in the case of catalysts containing extra-framework polynuclear Mn species and negligible in the case of Mn(I.E.) AlBEA containing predominantly isolated, extra-framework Mn(ii ) species.